2020
DOI: 10.1136/sextrans-2019-054327
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to hepatitis A among men who have sex with men attending a large sexual health clinic in Melbourne, Australia, 2012–2018

Abstract: BackgroundOutbreaks of hepatitis A are being reported more commonly among men who have sex with men (MSM) globally. Australia has also reported a sharp increase in the number of cases of hepatitis A in 2017. This study aimed to determine the level of immunity to hepatitis A among MSM attending a large urban sexual health clinic in Victoria in the lead up to recent outbreak.MethodsThis was a retrospective audit of serological testing data from first-time MSM attendees at Melbourne Sexual Health Centre (MSHC) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is similar to a recent study from Victoria, Australia, where they found that in their single tertiary sexual health service the susceptibility was 56%. 9 These estimates of susceptibility are worryingly above the predicted level at which outbreaks can occur. As rates of STI increase, more effort is needed to provide adequate herd immunity in MSM for hepatitis A.…”
Section: Discussionmentioning
confidence: 98%
“…This is similar to a recent study from Victoria, Australia, where they found that in their single tertiary sexual health service the susceptibility was 56%. 9 These estimates of susceptibility are worryingly above the predicted level at which outbreaks can occur. As rates of STI increase, more effort is needed to provide adequate herd immunity in MSM for hepatitis A.…”
Section: Discussionmentioning
confidence: 98%
“…Melbourne Sexual Health Centre (MSHC) is Victoria’s largest public sexual health clinic in Australia and offers free HIV/STI testing and management 34 . Men who reported having sex with men in the past 12 months were defined as MSM.…”
Section: Methodsmentioning
confidence: 99%
“…The Melbourne Sexual Health Centre (MSHC) is the largest public sexual health center in Victoria, Australia and offers free HIV and STI testing and management [32]. At the MSHC, individuals' demographic information and sexual practices are recorded using a computer-assisted self-interview (CASI) at each visit, at least 3 months apart [33].…”
Section: Study Populationmentioning
confidence: 99%